The theory of nucleation of polymer crystallization. Part II. The multidimensional theory of nucleation and its applications - Ziabicki, A. (Polimery, 2022)
Summary - The generalized multidimensional theory of phase transformations is discussed. Nucleation is treated as the motion of clusters in an N-di-mensional configurational space which comprises n dimensions of a growing cluster, three cluster orientation angles (Euler angles), the position of the mass center, and k-variables specific of the internal cluster structure. The generalized theory predicts some new mechanisms of nucleation involving rotation and translation of clusters in the external potential field and changes in internal structure (e.g., healing of internal defects). Illustrative applications are discussed, including selective crystallization in an oriented system, selective melting of pre-tensioned crystals, crystallization in the electric field and in the centrifuge’s gravitational field. Problems connected with crystallization morphology are discussed, viz., polymer crystal models and polymer morphology (comprising both folded-chain and bundle-like segments) in relation to polymer concentration.